2013
DOI: 10.1111/ijal.12021
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cultural universality and specificity on EFL learners' comprehension of metaphor and metonymy

Abstract: EFL learners may face different degrees of difficulty in transferring figurative expressions between L1 and L2 due to cultural similarities and differences embedded in languages. This study explores the influence of universality and specificity of culture on EFL learners' comprehension of metaphor and metonymy. Twenty eight Taiwanese EFL learners were asked to translate 12 English sentences into Chinese. Findings indicate that the participants performed the best when English and Chinese shared the same concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 26 publications
4
19
0
2
Order By: Relevance
“…The first question also concerned the effect of formal similarity between the L2 idioms and their L1 equivalents on comprehension. The results obtained in the present study consistently show that an increasing formal difference corresponds to a decrease in idiom comprehension, which generally concurs with previous studies (Türker, 2016;Chen and Lai, 2013;Yeganehjoo et al, 2012;Charteris-Black, 2002). However, we should sound a note of caution with regard to the consistency with previous results, since cross-linguistic formal differences have been defined in different ways: Whereas we used the term formal distance to refer to morphosyntactic differences between the L1 and the L2, other studies such as Türker (2016) used the term "linguistic distance" to denominate both morphosyntactic and semantic differences in the linguistic realization of a conceptual metaphor.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The first question also concerned the effect of formal similarity between the L2 idioms and their L1 equivalents on comprehension. The results obtained in the present study consistently show that an increasing formal difference corresponds to a decrease in idiom comprehension, which generally concurs with previous studies (Türker, 2016;Chen and Lai, 2013;Yeganehjoo et al, 2012;Charteris-Black, 2002). However, we should sound a note of caution with regard to the consistency with previous results, since cross-linguistic formal differences have been defined in different ways: Whereas we used the term formal distance to refer to morphosyntactic differences between the L1 and the L2, other studies such as Türker (2016) used the term "linguistic distance" to denominate both morphosyntactic and semantic differences in the linguistic realization of a conceptual metaphor.…”
Section: Discussionsupporting
confidence: 93%
“…at the feet of somebody') was often described in French as mettre des bâtons dans les roues ('to put sticks in the wheels'). In general, these findings align well with previous research (Türker, 2016;Chen and Lai, 2013;Charteris-Black, 2002;Liontas, 2002;Irujo, 1986), but contrast with the results of the study by De Cock and Suñer (2018), which indicate that cross-linguistic conceptual differences do not automatically lead to an impaired comprehension of metaphorical taboo expressions. Thus, future research should focus on whether the different degrees of conceptual distance also apply to such specific topic domains.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The results of studies in the field of idioms showed that L1 knowledge helps to understand identical and similar idioms, however it interferes in comprehension of completely different idioms and in the production of idioms in tests (Irujo, 1986;Charteris-Black, 2002;Chen & Lai, 2013). In addition, L1 influence on the use of idioms is higher at the beginning and at advanced stages of L2 learning (Kellerman, 1987).…”
Section: Epic Series In Language and Linguisticsmentioning
confidence: 99%